2008
DOI: 10.5380/avs.v13i2.11613
|View full text |Cite
|
Sign up to set email alerts
|

Dirofilariose Canina No Município De Coari, Estado Do Amazonas, Brasil.

Abstract: A dirofilariose representa um problema de saúde canina devido às sérias alterações orgânicas que ocasionam no hospedeiro infectado. A pesquisa de microfilárias em amostras de sangue de 120 cães mostrou que 12,5% estavam infectados, confirmando a existência do parasito no município de Coari. Esse estudo é o primeiro realizado na região do Médio Solimões necessitando que medidas preventivas sejam realizadas conforme a necessidade da localidade. Palavras-chave: Dirofilariose, Dirofilaria immitis, cão. A AB BS ST … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Interestingly, while the prevalence of infected dogs was 18.2% in the urban area, it varied from 40 to 83.3% among the rural areas (Table 3). Higher canine infection rates in rural than in urban areas were also reported in another study in the state of Amazonas, where Silva et al (2008b) found 4.3 and 42.3% of urban and rural dogs, respectively, infected by D. immitis. Similarly to the present study, the rural dogs sampled by Silva et al (2008b) were mostly owned by riverines; therefore, higher canine infection rates in rural than urban areas could be related to the closer proximity of large water collections because riverines' homes are typically over water during the 6-month flooding period every year.…”
Section: Discussionmentioning
confidence: 56%
“…Interestingly, while the prevalence of infected dogs was 18.2% in the urban area, it varied from 40 to 83.3% among the rural areas (Table 3). Higher canine infection rates in rural than in urban areas were also reported in another study in the state of Amazonas, where Silva et al (2008b) found 4.3 and 42.3% of urban and rural dogs, respectively, infected by D. immitis. Similarly to the present study, the rural dogs sampled by Silva et al (2008b) were mostly owned by riverines; therefore, higher canine infection rates in rural than urban areas could be related to the closer proximity of large water collections because riverines' homes are typically over water during the 6-month flooding period every year.…”
Section: Discussionmentioning
confidence: 56%
“…The infection was found more often among male dogs from one to three years old than among females within the same age range, which is not in line with other Brazilian studies that report not finding any differences between genders among infected animals (Almeida et al 2001, Silva et al 2008, Labarthe et al 2014. It is likely that females are cared for differently in Algodoal Island, which makes them less exposed to mosquitoes than males, or that they receive some protective treatment.…”
Section: Discussionmentioning
confidence: 57%
“…Humans and felines, which may be accidental hosts, are more susceptible to infection in areas with high prevalence of the canine disease (Garcez et al 2006, Mirahmadi et al 2017, which is distributed all over the globe (Bolio-Gonzalez et al 2007, Bowman & Atkins 2009, Hou et al 2011, Simsek et al 2011, Montoya-Alonso et al 2015, Bendas et al 2017. It has been found in every geographical region of Brazil, with prevalence rates over the last decade ranging from 2.1% in Florianópolis, in the Southern state of Santa Catarina (SC), to 62.2% in Armação de Búzios, in the Southeastern state of Rio de Janeiro (RJ) (Silva et al 2008, Dirofilaria immitis infection in dogs in Algodoal Island, Brazilian Amazon Furtado et al 2009, Ogawa et al 2013, Labarthe et al 2014, Soares et al 2014, Ramos et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Most areas are moist and warm, due to the influence of the flow rate of its large water bodies, such as the Amazon river. In Coari, AM, 12.5% (SILVA et al, 2008); in Lábrea, AM, 44.4% and in Porto Velho, RO, 12.8% (OGAWA et al, 2013) of the dogs were shown to be infected (Table 3).…”
Section: Resultsmentioning
confidence: 99%